Loss-of-function mutations in cause a new form of inherited thrombocytopenia. - Marconi, Caterina; Di Buduo, Christian A; LeVine, Kellie; Barozzi, Serena; Faleschini, Michela; Bozzi, Valeria; Palombo, Flavia; McKinstry, Spencer; Lassandro, Giuseppe; Giordano, Paola; Noris, Patrizia; Balduini, Carlo L; et al. (Blood, 2019)
Inherited thrombocytopenias (ITs) are a heterogeneous group of disorders characterized by low platelet count that may result in bleeding tendency. Despite progress being made in defining the genetic causes of ITs, nearly 50% of patients with familial thrombocytopenia are affected with forms of unknown origin. Here, through exome sequencing of 2 siblings with autosomal-recessive thrombocytopenia, we identified biallelic loss-of-function variants in This gene encodes for a receptor-like PTP, PTPRJ (or CD148), which is expressed abundantly in platelets and megakaryocytes. Consistent with the predicted effects of the variants, both probands have an almost complete loss of PTPRJ at the messenger RNA and protein levels. To investigate the pathogenic role of PTPRJ deficiency in hematopoiesis in vivo, we carried out CRISPR/Cas9-mediated ablation of (the ortholog of human ) in zebrafish, which induced a significantly decreased number of CD41 thrombocytes in vivo. Moreover, megakaryocytes of our patients showed impaired maturation and profound defects in SDF1-driven migration and formation of proplatelets in vitro. Silencing of in a human megakaryocytic cell line reproduced the functional defects observed in patients' megakaryocytes. The disorder caused by mutations presented as a nonsyndromic thrombocytopenia characterized by spontaneous bleeding, small-sized platelets, and impaired platelet responses to the GPVI agonists collagen and convulxin. These platelet functional defects could be attributed to reduced activation of Src family kinases. Taken together, our data identify a new form of IT and highlight a hitherto unknown fundamental role for PTPRJ in platelet biogenesis.

ACTN1 mutations lead to a benign form of platelet macrocytosis not always associated with thrombocytopenia. - Faleschini, Michela; Melazzini, Federica; Marconi, Caterina; Giangregorio, Tania; Pippucci, Tommaso; Cigalini, Elena; Pecci, Alessandro; Bottega, Roberta; Ramenghi, Ugo; Siitonen, Timo; Seri, Marco; Pastore, Annalisa; et al. (Br J Haematol, 2018)
The inherited thrombocytopenias (IT) are a heterogeneous group of diseases resulting from mutations in more than 30 different genes. Among them, ACTN1-related thrombocytopenia (ACTN1-RT; Online Mendelian Inheritance in Man: 615193) is one of the most recently identified forms. It has been described as a mild autosomal dominant macrothrombocytopenia caused by mutations in ACTN1, a gene encoding for one of the two non-muscle isoforms of α-actinin. We recently identified seven new unrelated families with ACTN1-RT caused by different mutations. Two of them are novel missense variants (p.Trp128Cys and p.Pro233Leu), whose pathogenic role has been confirmed by in vitro studies. Together with the 10 families we have previously described, our cohort of ACTN1-RT now consists of 49 individuals carrying ACTN1 mutations. This is the largest case series ever collected and enabled a critical evaluation of the clinical aspects of the disease. We concluded that ACTN1-RT is the fourth most frequent form of IT worldwide and it is characterized by platelet macrocytosis in all affected subjects and mild thrombocytopenia in less than 80% of cases. The risk of bleeding, either spontaneous or upon haemostatic challenge, is negligible and there are no other associated defects, either congenital or acquired. Therefore, ACTN1-RT is a benign form of IT, whose diagnosis provides affected individuals and their families with a good prognosis.

A new form of inherited thrombocytopenia due to monoallelic loss of function mutation in the thrombopoietin gene. - Noris, Patrizia; Marconi, Caterina; De Rocco, Daniela; Melazzini, Federica; Pippucci, Tommaso; Loffredo, Giuseppe; Giangregorio, Tania; Pecci, Alessandro; Seri, Marco; Savoia, Anna (Br J Haematol, 2018)

Mutations of RUNX1 in families with inherited thrombocytopenia. - De Rocco, Daniela; Melazzini, Federica; Marconi, Caterina; Pecci, Alessandro; Bottega, Roberta; Gnan, Chiara; Palombo, Flavia; Giordano, Paola; Coccioli, Maria Susanna; Glembotsky, Ana C; Heller, Paula G; Seri, Marco; et al. (Am J Hematol, 2017)
Keywords: Adult; Blood Platelets; Cell Size; Child; Child, Preschool; Core Binding Factor Alpha 2 Subunit; Female; Frameshift Mutation; Genes, Dominant; Heterozygote; Humans; Introns; Leukemia, Myeloid, Acute; Male; Middle Aged; Mutation, Missense; Protein Domains; RNA Splice Sites; Sequence Deletion; Thrombocythemia, Essential; Thrombopoietin; Transcriptional Activation; Young Adult

Clinical and pathogenetic features of ETV6 related thrombocytopenia with predisposition to acute lymphoblastic leukemia. - Melazzini, Federica; Palombo, Flavia; Balduini, Alessandra; De Rocco, Daniela; Marconi, Caterina; Noris, Patrizia; Gnan, Chiara; Pippucci, Tommaso; Bozzi, Valeria; Faleschini, Michela; Barozzi, Serena; Doubek, Michael; et al. (Haematologica, 2016)
ETV6-related thrombocytopenia (ETV6-RT) is an autosomal dominant thrombocytopenia that has been recently identified in a few families and has been suspected to predispose to hematological malignancies. To gain further information on this disorder, we searched for ETV6 mutations in the 130 families with inherited thrombocytopenia of unknown origin from our cohort of 274 consecutive pedigrees with familial thrombocytopenia. We identified 20 ETV6-RT patients from 7 pedigrees. They have 5 different ETV6 variants, including three novel mutations affecting the highly conserved E26 transformation-specific domain. The relative frequency of ETV6-RT resulted 2.6% in the whole case series and 4.6% among the families with known forms of inherited thrombocytopenia. The degree of thrombocytopenia and bleeding tendency of ETV6-RT patients were mild, but 4 subjects developed B-cell acute lymphoblastic leukemia during childhood, resulting in a significantly increased incidence compared to the general population. Clinical and laboratory findings did not identify any peculiar defects that can be used to suspect this disorder by routine diagnostic workup. However, at variance with most inherited thrombocytopenias, platelet size was not enlarged. In vitro studies revealed that patients megakaryocytes have defective maturation and impaired proplatelet formation. Moreover, ETV6-RT platelets have reduced ability to spread on fibrinogen. Since also the dominant thrombocytopenias due to mutations in RUNX1 and ANKRD26 are characterized by normal platelet size and predispose to hematological malignancies, we suggest that mutation screening of ETV6, RUNX1 and ANKRD26 should be performed in all the subjects with autosomal dominant thrombocytopenia and normal platelet size.

ACTN1-related thrombocytopenia: identification of novel families for phenotypic characterization. - Bottega, Roberta; Marconi, Caterina; Faleschini, Michela; Baj, Gabriele; Cagioni, Claudia; Pecci, Alessandro; Pippucci, Tommaso; Ramenghi, Ugo; Pardini, Simonetta; Ngu, Loretta; Baronci, Carlo; Kunishima, Shinji; et al. (Blood, 2015)
Inherited thrombocytopenias (ITs) are a heterogeneous group of syndromic and nonsyndromic diseases caused by mutations affecting different genes. Alterations of ACTN1, the gene encoding for α-actinin 1, have recently been identified in a few families as being responsible for a mild form of IT (ACTN1-related thrombocytopenia; ACTN1-RT). To better characterize this disease, we screened ACTN1 in 128 probands and found 10 (8 novel) missense heterozygous variants in 11 families. Combining bioinformatics, segregation, and functional studies, we demonstrated that all but 1 amino acid substitution had deleterious effects. The clinical and laboratory findings of 31 affected individuals confirmed that ACTN1-RT is a mild macrothrombocytopenia with low risk for bleeding. Low reticulated platelet counts and only slightly increased serum thrombopoietin levels indicated that the latest phases of megakaryopoiesis were affected. Given its relatively high frequency in our cohort (4.2%), ACTN1-RT has to be taken into consideration in the differential diagnosis of ITs.
Keywords: Actinin; Adolescent; Adult; Aged; Aged, 80 and over; Blood Platelets; Case-Control Studies; Child; Child, Preschool; Female; Gene Expression; Genotype; Heterozygote; Humans; Male; Middle Aged; Mutation, Missense; Pedigree; Phenotype; Platelet Count; Severity of Illness Index; Thrombocytopenia; Thrombopoiesis; Thrombopoietin

MYH9-related disease: a novel prognostic model to predict the clinical evolution of the disease based on genotype-phenotype correlations. - Pecci, Alessandro; Klersy, Catherine; Gresele, Paolo; Lee, Kieran J D; De Rocco, Daniela; Bozzi, Valeria; Russo, Giovanna; Heller, Paula G; Loffredo, Giuseppe; Ballmaier, Matthias; Fabris, Fabrizio; Beggiato, Eloise; et al. (Hum Mutat, 2014)
MYH9-related disease (MYH9-RD) is a rare autosomal-dominant disorder caused by mutations in the gene for nonmuscle myosin heavy chain IIA (NMMHC-IIA). MYH9-RD is characterized by a considerable variability in clinical evolution: patients present at birth with only thrombocytopenia, but some of them subsequently develop sensorineural deafness, cataract, and/or nephropathy often leading to end-stage renal disease (ESRD). We searched for genotype-phenotype correlations in the largest series of consecutive MYH9-RD patients collected so far (255 cases from 121 families). Association of genotypes with noncongenital features was assessed by a generalized linear regression model. The analysis defined disease evolution associated to seven different MYH9 genotypes that are responsible for 85% of MYH9-RD cases. Mutations hitting residue R702 demonstrated a complete penetrance for early-onset ESRD and deafness. The p.D1424H substitution associated with high risk of developing all the noncongenital manifestations of disease. Mutations hitting a distinct hydrophobic seam in the NMMHC-IIA head domain or substitutions at R1165 associated with high risk of deafness but low risk of nephropathy or cataract. Patients with p.E1841K, p.D1424N, and C-terminal deletions had low risk of noncongenital defects. These findings are essential to patients' clinical management and genetic counseling and are discussed in view of molecular pathogenesis of MYH9-RD.
Keywords: Adult; Age of Onset; Amino Acid Substitution; Cataract; Female; Genetic Association Studies; Genotype; Hearing Loss, Sensorineural; Humans; Italy; Linear Models; Male; Molecular Motor Proteins; Mutation; Myosin Heavy Chains; Phenotype; Risk Factors; Thrombocytopenia

Platelet diameters in inherited thrombocytopenias: analysis of 376 patients with all known disorders. - Noris, Patrizia; Biino, Ginevra; Pecci, Alessandro; Civaschi, Elisa; Savoia, Anna; Seri, Marco; Melazzini, Federica; Loffredo, Giuseppe; Russo, Giovanna; Bozzi, Valeria; Notarangelo, Lucia Dora; Gresele, Paolo; et al. (Blood, 2014)
Abnormalities of platelet size are one of the distinguishing features of inherited thrombocytopenias (ITs), and evaluation of blood films is recommended as an essential step for differential diagnosis of these disorders. Nevertheless, what we presently know about this subject is derived mainly from anecdotal evidence. To improve knowledge in this field, we evaluated platelet size on blood films obtained from 376 patients with all 19 forms of IT identified so far and found that these conditions differ not only in mean platelet diameter, but also in platelet diameter distribution width and the percentage of platelets with increased or reduced diameters. On the basis of these findings, we propose a new classification of ITs according to platelet size. It distinguishes forms with giant platelets, with large platelets, with normal or slightly increased platelet size, and with normal or slightly decreased platelet size. We also measured platelet diameters in 87 patients with immune thrombocytopenia and identified cutoff values for mean platelet diameter and the percentage of platelets with increased or reduced size that have good diagnostic accuracy in differentiating ITs with giant platelets and with normal or slightly decreased platelet size from immune thrombocytopenia and all other forms of IT.
Keywords: Adolescent; Adult; Blood Platelets; Case-Control Studies; Cell Size; Child; Child, Preschool; Diagnosis, Differential; Female; Hearing Loss, Sensorineural; Humans; Infant; Male; Middle Aged; Molecular Motor Proteins; Mutation; Myosin Heavy Chains; Purpura, Thrombocytopenic, Idiopathic; Thrombocytopenia; Young Adult

Mutations in ANKRD26 are responsible for a frequent form of inherited thrombocytopenia: analysis of 78 patients from 21 families. - Noris, Patrizia; Perrotta, Silverio; Seri, Marco; Pecci, Alessandro; Gnan, Chiara; Loffredo, Giuseppe; Pujol-Moix, Núria; Zecca, Marco; Scognamiglio, Francesca; De Rocco, Daniela; Punzo, Francesca; Melazzini, Federica; et al. (Blood, 2011)
Until recently, thrombocytopenia 2 (THC2) was considered an exceedingly rare form of autosomal dominant thrombocytopenia and only 2 families were known. However, we recently identified mutations in the 5'-untranslated region of the ANKRD26 gene in 9 THC2 families. Here we report on 12 additional pedigrees with ANKRD26 mutations, 6 of which are new. Because THC2 affected 21 of the 210 families in our database, it has to be considered one of the less rare forms of inherited thrombocytopenia. Analysis of all 21 families with ANKRD26 mutations identified to date revealed that thrombocytopenia and bleeding tendency were usually mild. Nearly all patients had no platelet macrocytosis, and this characteristic distinguishes THC2 from most other forms of inherited thrombocytopenia. In the majority of cases, platelets were deficient in glycoprotein Ia and α-granules, whereas in vitro platelet aggregation was normal. Bone marrow examination and serum thrombopoietin levels suggested that thrombocytopenia was derived from dysmegakaryopoiesis. Unexplained high values of hemoglobin and leukocytes were observed in a few cases. An unexpected finding that warrants further investigation was a high incidence of acute leukemia. Given the scarcity of distinctive characteristics, the ANKRD26-related thrombocytopenia has to be taken into consideration in the differential diagnosis of isolated thrombocytopenias.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Ankyrin Repeat; Child; Cohort Studies; Family; Female; Gene Frequency; Humans; Inheritance Patterns; Male; Middle Aged; Mutation; Pedigree; Thrombocytopenia; Transcription Factors; Young Adult

Mutations in the 5' UTR of ANKRD26, the ankirin repeat domain 26 gene, cause an autosomal-dominant form of inherited thrombocytopenia, THC2. - Pippucci, Tommaso; Savoia, Anna; Perrotta, Silverio; Pujol-Moix, Núria; Noris, Patrizia; Castegnaro, Giovanni; Pecci, Alessandro; Gnan, Chiara; Punzo, Francesca; Marconi, Caterina; Gherardi, Samuele; Loffredo, Giuseppe; et al. (Am J Hum Genet, 2011)
THC2, an autosomal-dominant thrombocytopenia described so far in only two families, has been ascribed to mutations in MASTL or ACBD5. Here, we show that ANKRD26, another gene within the THC2 locus, and neither MASTL nor ACBD5, is mutated in eight unrelated families. ANKRD26 was also found to be mutated in the family previously reported to have an ACBD5 mutation. We identified six different ANKRD26 mutations, which were clustered in a highly conserved 19 bp sequence located in the 5' untranslated region. Mutations were not detected in 500 controls and are absent from the 1000 Genomes database. Available data from an animal model and Dr. Watson's genome give evidence against haploinsufficiency as the pathogenetic mechanism for ANKRD26-mediated thrombocytopenia. The luciferase reporter assay suggests that these 5' UTR mutations might enhance ANKRD26 expression. ANKRD26 is the ancestor of a family of primate-specific genes termed POTE, which have been recently identified as a family of proapoptotic proteins. Dysregulation of apoptosis might therefore be the pathogenetic mechanism, as demonstrated for another thrombocytopenia, THC4. Further investigation is needed to provide evidence supporting this hypothesis.
Keywords: Ankyrin Repeat; Base Sequence; Chromosome Breakage; Chromosome Disorders; Conserved Sequence; Female; Genes, Dominant; Genetic Loci; Haploinsufficiency; Humans; Male; Molecular Sequence Data; Mutation; Pedigree; Thrombocytopenia